Facile synthesis of visible region luminescent silver decorated graphene oxide nanohybrid for biomedical applications: In combination with DFT calculations. (2022) - Joy, Anjumol; Unnikrishnan, Gayathri; Megha, M.; devi Duraisamy, Parimala; Angamuthu, Abiram; Haris, M.; Kolanthai, Elayaraja; Muthuswamy, Senthilkumar
Abstract: Nanohybrid materials derived from silver nanoparticles (Ag-NPs) and graphene oxide (GO) attract substantial research consideration on account of their promising role in the biomedical field. The present study demonstrates an effectual method for decoration of silver nanoparticles over GO surface via an in-situ method, performed in an inert atmosphere. The incorporation of AgNPs on the GO surface was validated by various characterization techniques like XRD, SEM, EDAX, FTIR, and Raman analysis. The distribution of AgNPs on graphene sheets with lamellar morphology was observed. The Raman spectrum for Ag-GO nanohybrid was remarkably augmented, which owes to the existence of silver nanoparticles. The PL emission peaks of Ag-GO nanoparticles recorded around 418 and 440 nm ascribed to the interface of the localized surface plasmon resonance (LSPR) of silver nanoparticles and the inherent luminescence of GO. The density functional theory calculations (DFT) were executed for further understanding the HOMO-LUMO energy, adsorption energy and molecular structure of GO with Ag + . Additionally, the Ag-GO nanohybrid exhibited distinguishable antibacterial efficacy against E. coli (gram −ve) and S. aureus (gram +ve), in contrast to the results obtained for pristine GO, due to the synergistic impact of perforation of the bacterial wall by GO and silver ion release. The remarkable luminescent behaviour and antibacterial property of the as-synthesized Ag-GO nanohybrid reveal that it can be potentially used as a multifunctional weapon in the biomedical field.